A comparative study of microstrain around three-morse taper implants with machined and plastic copings under axial loading - de Abreu, Celina Wanderley; de Vasconcellos, Luis Gustavo Oliveira [UNESP]; Balducci, Ivan [UNESP]; Nishioka, Renato Sussumu [UNESP] (My University, 2013)
Aim: To evaluate the occurrence of microstrain around morse taper implants in straight configuration under axial load in a cast monoblock framework. Methods: Three implants were inserted in a polyurethane block and microunit abutments were installed on the implants with 20 Ncm torque. Plastic and machined copings were adapted on the preset waxing to fabricate the framework (n=5). Four strain gauges were attached on the upper surface of the block and then each framework was tightened on the abutments and a vertical load of 30 kg was applied to five points of the framework. Results: The data obtained in the strain gauge analysis were subjected to twoway ANOVA and Tukey's test (α=0.05). There was statistically significant difference (p=0.0222) for the factor application point and the mean microstrain values were: application point B 402,04μσ, point A 401.21μσ, point E 390.44μσ , point D 341.76μσ and point C 309.19 μσ. Conclusions: There was no microstrain difference between plastic and machined copings during axial loading. Difference in the application point was observed, but remained within bone physiological limits.
Keywords: Axial load; Dental implant; Fixed prosthesis; Morse taper; Strain gauge